Outpatient Procedures on the Glans and Anterior Urethra Under a New Local Anaesthesia: Intracorpus Spongiosum Anaesthesia - Gang Ye; Wang Xiang-Wei; Yi Shan-Hong; Zhang Yong-Gui; Liu Wei-Chi (Asian Journal of Surgery, 2005)
To determine the efficacy of intracorpus spongiosum anaesthesia during minor procedures on the glans and anterior urethra in the outpatient clinic. Methods: Sixty-nine consecutive male patients underwent various procedures on the glans penis or anterior urethra under intracorpus spongiosum anaesthesia, which was performed by injection of 3 mL of 1% lidocaine into the glans penis. The effect of this anaesthetic technique was assessed by questionnaire using a pain scale. Results: Following injection of lidocaine, the anaesthetic effect was immediate and very satisfactory. The minor procedures, varying from 8 to 68 minutes in duration, were successfully completed under the new local anaesthesia. Of the 69 patients, 63 (91.3%) felt no pain and six (8.7%) reported either minor or moderate discomfort that was tolerable and could be ignored. There were no serious complications with this anaesthetic technique except for three patients (4.3%) who had instantaneous trance during lidocaine injection. Conclusion: Intracorpus spongiosum anaesthesia is an effective, simple, safe anaesthetic technique for minor procedures on the glans and anterior urethra in an outpatient setting. With this new local anaesthesia, the total cost of many procedures on the glans and anterior urethra can be markedly reduced.